1987
DOI: 10.1107/s0108767387099963
|View full text |Cite
|
Sign up to set email alerts
|

Figures of merit in direct methods: a new point of view

Abstract: The probabilistic approach has been extensively used for analysing the statistical meanings of some traditional figures of merit. New figures of merit have also been introduced; some exploit one-phase and twophase structure seminvariants of the first rank, the expected negative and/or enantiomorph-sensitive triplet invariants, and the expected negative and/or enantiomorph-sensitive quartets. Other figures of merit exploit the distribution of statistical parameters connected with PSI(0) and active triplets. A n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

1987
1987
2007
2007

Publication Types

Select...
6
4

Relationship

5
5

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 8 publications
0
16
0
2
Order By: Relevance
“…The reliability of the various triplets was first estimated according to the second representation formula /1o (Cascarano, Giacovazzo, Camalli, Spagna, Burla, Nunzi & Polidori, 1984). Triplets estimated as positive were actively used in the phasing process while triplets estimated as negative were used as a figure of merit (Cascarano, Giacovazzo & Viterbo, 1987). For each structure only 100 routinary trials were made: in column 7 the number of respective solutions is shown.…”
Section: Experimental Results and Conclusionmentioning
confidence: 99%
“…The reliability of the various triplets was first estimated according to the second representation formula /1o (Cascarano, Giacovazzo, Camalli, Spagna, Burla, Nunzi & Polidori, 1984). Triplets estimated as positive were actively used in the phasing process while triplets estimated as negative were used as a figure of merit (Cascarano, Giacovazzo & Viterbo, 1987). For each structure only 100 routinary trials were made: in column 7 the number of respective solutions is shown.…”
Section: Experimental Results and Conclusionmentioning
confidence: 99%
“…when no prior information is available, and it is only necessary that the fractional part of hr be uniformly distributed in the interval (0, 1)]. On the other hand prior information often breaks down the symmetry of the roles, so that the two distributions are deeply different [for example, when a structural fragment has a known position (Giacovazzo, 1983), or when superstructural effects are present (Cascarano, Giacovazzo & Lui6, 1985, 1987]. Symmetrization of the roles is still possible but some supplementary conditions on the reciprocal vectors are needed if they are used as primitive random va.riables.…”
Section: H+k+l=0 (2)mentioning
confidence: 99%
“…Some FOMs, like the well known MABS, ABSFOM, R,~ and NALF (Declercq, Germain & Woolfson, 1979;Karle & Karle, 1966;Cascarano, Giacovazzo & Viterbo, 1987) check if the distribution of the O~3,h'S fitS the expected distribution. On the same principle are based the so-called psi(0) FOMs (Cochran & Douglas, 1957;Cascarano, Giacovazzo & Guagliardi, 1992) while the negative-quartet criterion (DeTitta, Edmonds, Langs & Hauptman, 1975;Cascarano, Giacovazzo & Viterbo, 1987) relies on the expectation that some quartet invariants are negative.…”
Section: Violation Of the Positivity Condition: Its Effect On Tripletmentioning
confidence: 99%